Career Management Issues Facing Expatriates - Feldman, Daniel C.; Thomas, David C. (Journal of International Business Studies, 1992)
This research explores expatriate assignments from a career development perspective. First, the article examines the impact of five organization-level career development programs and policies on expatriate effectiveness. Then, it explores the impact of five individual-level career management strategies on the success of expatriate transitions. Data from 118 expatriates in Saudi Arabia, Europe, South America, and Japan are presented to examine these career development issues.